Investigation of magnetite concentrate utilization as reinforcement in aluminum matrix composites - Birol, Burak; Misirlioglu, Banu Sungu; Cakir, Oznur (SAGE PUBLICATIONS LTD, 2022)
The utilization of harder particles with magnetic properties as reinforcement in aluminum matrix composites (AMCs) enhances the mechanical and magnetic properties of aluminum. Present study investigates the utilization of magnetite concentrate (MC), which is composed of mainly Fe3O4, as reinforcement in AMCs. To achieve this goal, commercially pure Al and MC powders were blended (0-40 wt.% of MC) and ground by high energy ball milling, pressed, and sintered at 600 degrees C for 30 min under an argon atmosphere. The products were characterized by XRD, and SEM analyses. Also, the density and porosity of the samples were determined by Archimedes' principle. According to the results, it was observed that with the increasing reinforcement amount, agglomeration of the MC particles inside the Al matrix, as well as the porosities of the samples, increased. 10-20 wt. % of MC containing samples, the porosity values were obtained around 12 vol. %, however higher reinforcement amounts, raised the porosity values to 17.33 vol. % linearly. With the increment in both nonconductive MC particles and pores, the electrical conductivity of the samples decreased linearly. On the other hand, hard reinforcement particles played a positive role in both hardness and wear properties and a 43.37 HB of hardness value and 0.197 m(3)/N.m x 10(-12) specific wear rate was obtained for the sample containing 40 wt. %, MC. In addition, an increase in magnetic properties was observed in direct proportion to the amount of MC particles added, up to 31 Am-2.kg(-1) of saturation magnetization.
Keywords: Aluminum matrix composites; magnetite concentrate; powder metallurgy; mechanical properties; electrical conductivity; magnetic properties; MECHANICAL-PROPERTIES; ELECTRICAL-CONDUCTIVITY; POWDER-METALLURGY; FABRICATION METHODS; MICROSTRUCTURE; FE3O4; NANOPARTICLES; WEAR; SIZE; PARTICLES; Materials Science